Computed Tomography and Adrenal Venous Sampling in the Diagnosis of Unilateral Primary Aldosteronism. Issue 3 (September 2018) - Williams, Tracy A.; Burrello, Jacopo; Sechi, Leonardo A.; Fardella, Carlos E.; Matrozova, Joanna; Adolf, Christian; Baudrand, René; Bernardi, Stella; Beuschlein, Felix; Catena, Cristiana; Doumas, Michalis; Fallo, Francesco; et al.
Abstract : Unilateral primary aldosteronism is the most common surgically correctable form of endocrine hypertension and is usually differentiated from bilateral forms by adrenal venous sampling (AVS) or computed tomography (CT). Our objective was to compare clinical and biochemical postsurgical outcomes of patients with unilateral primary aldosteronism diagnosed by CT or AVS and identify predictors of surgical outcomes. Patient data were obtained from 18 internationally distributed centers and retrospectively analyzed for clinical and biochemical outcomes of adrenalectomy of patients with surgical management based on CT (n=235 patients, diagnosed from 1994–2016) or AVS (526 patients, diagnosed from 1994–2015) using the standardized PASO (Primary Aldosteronism Surgical Outcome) criteria. Biochemical outcomes were highly different according to surgical management approach with a smaller proportion in the CT group achieving complete biochemical success (188 of 235 [80%] patients versus 491 of 526 [93%], P <0.001) and a greater proportion with absent biochemical success (29 of 235 [12%] versus 10 of 526 [2%], P <0.001). A diagnosis by CT was associated with a decreased likelihood of complete biochemical success compared with AVS (odds ratio, 0.28; 0.16–0.50; P <0.001). Clinical outcomes were not significantly different, but the absence of a postsurgical elevated aldosterone-to-renin ratio was a strong marker of complete clinical success (odds ratio, 14.81; 1.76–124.53; P =0.013) in the CT but not in the AVS group. In conclusion, patients diagnosed by CT have a decreased likelihood of achieving complete biochemical success compared with a diagnosis by AVS. Abstract : Supplemental Digital Content is available in the text.